Nurse-managed supportive cancer care and psychosocial adaption among patients with breast cancer - Gaspar-San Juan, Charity Leene
This study sought to develop a nurse-managed supportive cancer care intervention focusing on the informational, psycho-emotional and social support needs of patients with breast cancer and determined its effects on their psychosocial adaptation. This study employed a quasi-experimental study and utilized a pre test-post test design to examine the effects of the nurse-managed interventions. The study was conducted in a small support group facility based in Davao City, Philippines. The sample was comprised of fifty (50) patients purposively recruited. The researcher utilized a survey questionnaire to gather information about the demographic profile, disease-related characteristics and psychosocial adaptation of these patients. The measurement of psychosocial adaptation was based on the standard tool Psychosocial Adjustment to Illness Scale - Self Report (PAIS-SR), a structured and validated survey questionnaire to measure the study participants’ level of psychosocial adaptation. -- Results indicated that there were psychosocial adaptation differences (p>0.05) among breast cancer patients before and after the nurse-managed interventions. Chief differences were noted on the following six domains: health care orientation, vocational environment, domestic environment, extended family relationships, social environment and psychological distress. However, results indicated that there was no psychosocial adaptation difference in the domain of sexual relationships. -- Comparison between study and control group after nurse-managed cancer care intervention showed that there was an existing significant difference (p>0.05) on the level of psychosocial adaptation between two groups on the following psychosocial domains: health care orientation, vocation environment, domestic environment and psychological distress. On the other hand, no significant differences were obtained for three domains: sexual relationship, extended family relationship and social environment. -- There was no existing significant difference (p<0.05) among patients between study group and control group when analyzed by their age, civil status, income, educational attainment, disease phase and type of treatment. Therefore, it was found that both the study and control groups were statistically comparable. -- During the counseling sessions, a dominant theme emerged from the verbal accounts of the participants which was resentment. This was generally negative and critical attitudes to oneself, to family and to their faith. Lastly, during the group support sessions, coping functioning and understanding among patients and their families apparently was not obtained. Thus, family dynamics and support relationships should be incorporated to enhance coping in these areas. Moreover, the researcher of this study, has found that the participants when reporting accounts of their cancer experience during the counselling and group support sessions, were less more concealing and were more direct into answering questions. The researcher understood that the resentment stemmed from how cancer evolved as a disease process. Although etiology and duration of illness is a long term process, the diagnosis and the impact of the illness to them was sudden and unexpected. Recommendations were made after the relevant findings of this study.